Sport and risk of amyotrophic lateral sclerosis - Iłżecka, Joanna (Journal of Education, Health and Sport, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease affecting motor neurons. Symptoms of the disease include progressive weakness and atrophy of muscles and increasing respiratory failure. The etiology of the disease is not completely unknown. Data from the literature suggest that sport can be a risk factor for ALS through vigorous physical activity, trauma or micro trauma associated with it, and the acceptance by athletes toxic substances. Research on this topic conducted in patients with ALS are not clear, but some of them point to the importance of vigorous physical activity and traumatic factors in causing disease. The above issues require further research. The aim of the work was a review of the literature concerning sports and risk of ALS.